PREVALENCE AND RISK FACTORS OF DEPRESSION IN DIALYSIS DEPENDANT CKD PATIENTS (The Research of Medical Science Review, 2025)
Background: Depression is a prevalent yet underdiagnosed comorbidity in dialysis-dependent chronic kidney disease (CKD) patients, significantly impacting their quality of life and treatment outcomes. Objective: To determine the prevalence of depression and identify associated risk factors in patients with end-stage renal disease (ESRD) undergoing maintenance dialysis. Methods: A cross-sectional observational study was conducted at Bahria International Hospital from March to December 2024. A total of 332 adult dialysis-dependent CKD patients were assessed using the Patient Health Questionnaire-9 (PHQ-9). Clinically significant depression was defined as a PHQ-9 score ≥10. Logistic regression analysis was performed to identify independent risk factors. Results: The prevalence of clinically significant depression was 38.3%, with 6.0% of patients exhibiting severe depression (PHQ-9 score 20–27). Female gender (adjusted odds ratio [aOR]=2.10, 95% CI: 1.45–3.05, p<0.001), age ≥60 years (aOR=1.75, 95% CI: 1.20–2.55, p=0.003), dialysis duration >1 year (aOR=1.60, 95% CI: 1.10–2.33, p=0.015), low serum albumin (<3.5 g/dL; aOR=1.85, 95% CI: 1.25–2.74, p=0.002), unemployment (aOR=1.90, 95% CI: 1.30–2.78, p=0.001), and comorbid diabetes (aOR=1.50, 95% CI: 1.05–2.14, p=0.025) were significantly associated with depression. Conclusion: Depression is highly prevalent among dialysis-dependent CKD patients, with identifiable demographic, clinical, and socioeconomic risk factors. Routine screening and targeted interventions, particularly for high-risk subgroups, are essential to improve mental health and overall outcomes in this population.